The dialectics of the neo-neo debate in the neoliberal moment - Kassem, Sarrah (AUC Knowledge Fountain, 2015)
My thesis applies a historical materialist and dialectical analysis to the study of IR by holding the moment of the 1980s as temporally stable to study the debate between Neorealism and Neoliberalism (Neo-Neo debate). I ask two foundational and interrelated questions: 1) how are the material conditions of the neoliberal moment dialectically related to the reassertion of bourgeois mental conceptions in International Relations?; and 2) how does the ontology of dominant IR theory, understood as the Neo-Neo debate, lead to the exclusion of class analysis altogether? By studying the dialectical relations of the material context and the Neo-Neo debate, I argue that the reassertion of bourgeois mental conceptions, through the fetishistic individual ontology of the Neo-Neo debate in IR, contributes to the restoration of class power and extends the trajectory of capitalism’s survival in the neoliberal moment, by effectively denying the existence of class relations on a global scale. IR and its developments must be recognized as peculiar in, corresponding to and co-evolving with the historical moment that naturalizes its conceptualizations of the international order and as dialectically related to the material conditions of that historical moment. Only by doing so, is a move away from this fetishistic view, and towards a post-IR study of global relations based on a social ontology, made possible.